Longevity gap, indexation and age-specific average pensions - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2022)
Studying the age-dimension of the probability distribution of pensions while assuming steadily rising real wages and time-invariant benefit-rules, two factors play important roles: (i) the weight of the wages in indexation of benefits in progress; (ii) the longevity gap. Factor (i) acts against relative depreciation of older benefits, while factor (ii) raises the share of higher benefits among older cohorts. Using an example and a model we show how the shape of the average benefit–age-curve depends on the relation between these two factors.
Keywords: H55; 330; public pension system; longevity gap; indexation of pensions in progress; agespecific pensions